Dualism of the Aging Process (analytical review) - V. N. Shabalin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
The aging process is one of the most complex problems in biology. Hundreds of research institutes around the world are studying aging at various levels of the structural organization of living matter. The results of many thousands of studies on this phenomenon have been published. More than 300 theories have been proposed that attempt to explain the causes of aging. It is important to note that almost all theories associate aging with the accumulation of negative changes in molecules and cells in the body. It seems that a person (or an individual of another biological species) lives in order to make negative changes in the structure of living matter. However, this contradicts the fact that damage and destructive changes cannot ensure progress in the evolutionary development of life. The article attempts to find the cause of this contradiction. The author puts forward a position on the dual function of the aging process in the development of living matter: on the one hand, aging causes degradation of the organism as a system, on the other, it ensures the structural improvement of its tissues at the molecular level. That is, aging, as the main mechanism of evolution, is aimed not at preserving the organism as a system, but at preserving its individual elements (information blocks) that are of interest for building new structures of living matter as a whole. An evolutionary ladder is formed from these information blocks, along which living matter rises to a higher level of its development. Aging is not decay or damage, but a mechanism for transferring one structure of living tissue to another - more perfect, with its preservation in the form of a potential phase for use by new cellular generations of the same organism or other organisms.